O controle não judicial de políticas públicas como instrumento de efetividade do direito fundamental à saúde - Silva, Natel Laudo da (2022)
The present work, within the scope of the Human and Fundamental Rights, aims to outline extrajudicial alternatives for controlling public policies that serve as an instrument for the effectiveness of the right to health. The objective is to demonstrate that, in addition to a still inefficient performance of political powers and an overloaded jurisdictional control and essentially focused on microjustice, there are viable nonjudicial instruments in the Democratic State of Law for the control of social policies that can cooperate in effectiveness. of the constitutional right to health. For the proposed study, the deductive method was adopted, based on a bibliographical, explanatory research, essentially qualitative, with timely use of quantitative data. The theoretical framework and results obtained made it possible to draw foundations that establish the right to health as a human, fundamental and social right, with a markedly provisional essence; and to propose the definition of the effectiveness or social efficacy of the right to health, to be obtained through public policies, in order to materialize constitutional and legal precepts in the world of facts, bringing the normative mustbe closer to the social reality. In the present research, public policies are also presented as a new normative standard and planning instrument in its essence, serving as a means of effectiveness of social rights such as health, being imperative for this desideratum elements of internal control (voluntary selfrestraint) and external (social and institutional). With the indication of extrajudicial instruments of control aimed at macrojustice and protection of the collective interest, it is proposed not to prioritize the judicial control of public policies, in aversion to exacerbated judicial activism, excessive appreciation of microjustice and trivialization of principles, to give rise to perspectives such as selfrestraint and judicial moderation. The instruments of extrajudicial control of public health policies include social control through popular participation; selfcompositional control through the methods of administrative mediation and conciliation; external control, by the audit courts, based on operational audits and management adjustment terms, and by the Public Ministry, with the adoption of conduct adjustment terms; and the internal control in the public administration with reinforcement in the exercise of its activities by the compliance.